2021
DOI: 10.1371/journal.pgph.0000097
|View full text |Cite
|
Sign up to set email alerts
|

Self-care knowledge, attitude and associated factors among outpatients with diabetes mellitus in Arsi Zone, Southeast Ethiopia

Abstract: Introduction Diabetes mellitus is a chronic illness that requires continuing medical care and ongoing patient self-management, education and support to prevent acute complications and to reduce the risk of long-term complications. Therefore, this study aims to assess the self-care knowledge, attitude and associated factors among outpatients with diabetes mellitus in Arsi Zone, Southeast Ethiopia. Materials and methods A cross sectional study was employed in Arsi Zone, Southeast Ethiopia from April to June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Therefore, majority of respondents who had a negative attitude also had poor self-care practices. These findings are similar to the findings of Kassa [13],…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…Therefore, majority of respondents who had a negative attitude also had poor self-care practices. These findings are similar to the findings of Kassa [13],…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…Similarly, other previous studies have also shown a positive association between increased level of education and positive attitude [1,11,12]. However, some studies have shown lack of association between level of education and positive attitude on diabetes [23,33]. This discrepancy may be due to lack of uniformity in grading or scoring of level of education and patients having various levels of understanding regarding diabetes which brings heterogeneity.…”
Section: Plos Global Public Healthmentioning
confidence: 83%